Takhrij Hadis Karakteristik Muslimah dalam Kitab Syakhshiyah al-Mar’ah al-Muslimah Karya Muhammad Ali Al-Hasyimi - Nurhayati, Nurhayati (Jurnal Riset Agama, 2022)
The book Syakshiyah al-Mar'ah al-Muslimah by Muhammad Ali al-Hasyimi discusses the ideal character of a Muslim woman. In this book, he includes verses of the Qur'an and traditions related to the character of Muslim women. This study aims to determine the quality of the hadiths regarding the characteristics of Muslim women listed in the book of Syakhshiyah al-Mar'ah al-Muslimah by Muhammad Ali Al-Hasyimi. This type of research is qualitative through literature study using the takhrij hadith method and descriptive analysis approach. The takhrij method used is the takhrij hadith bi al-lafdzi, which is a search using some words from the matan hadith. The results and discussion of this research include an overview of the characteristics of Muslim women, editorials on the characteristics of Muslim women and takhrij hadiths which discuss the authenticity status of hadiths. Based on their authenticity and validity, this study concludes that the quality of the traditions contained in the book Syakhshiyah al-Mar'ah al-Muslimah by Muhammad Ali al-Hasyimi, is proven to be valid because it can be ascertained that the narrators are tsiqah and the hadiths are authentic. Therefore, these traditions can be used as syara' arguments or evidence in Islamic law for every Muslim woman who always explores her character. According to al-Hasyimi, the characteristics that a Muslim woman must have include 1) maintaining her honor; 2) obedient to parents and husband; 3) establish a good relationship.